Does family reunification from residential care facilities serve children's best interest? A propensity-score matching approach in Ghana. (December 2017) - James, Spencer L.; Roby, Jini L.; Powell, Lindsay J.; Teuscher, Bryan A.; Hamstead, Kelsey L.; Shafer, Kevin
Abstract: The U.N. Convention on the Rights of the Child declares that children are entitled to grow up in a family environment with love, happiness and understanding. Governments and international child welfare agencies have promoted the reintegration of children currently in residential care facilities with family or other caregivers. We assess whether 157 children who spent time in a Ghanaian residential care facility but who have been reunified with their families scored differently on a battery of standardized child wellbeing measures than 204 children still living in residential care facilities using propensity score matching models. Results suggest that outcomes, including overall hope (as well as hope pathways and hope agency) and access to basic resources as measured on the Child Status Index, differ between children who were and were not reunified. These results underline the importance of supporting children's physical and psychosocial developmental needs. Children who were reunified with family members or other kin may require additional support regarding access to basic resources whereas interventions designed to increase hope in the future may benefit children in residential care. We urge a redoubling of efforts to care for children under carefully designed national schemes providing resources, trained personnel, and sustained case management. Highlights: Child wellbeing outcomes differ between reunified children and children who remain in the orphanages. Children in residential care facilities (RCFs) reported better access to basic resources than their reunified counterparts. Reunified children reported higher levels of overall hope as well as hope pathways and hope agency.